Conjoint trajectories of depressive symptoms and delinquent behavior predicting substance use disorders. (March 2015) - Brook, Judith S.; Lee, Jung Yeon; Finch, Stephen J.; Brook, David W.
Abstract: Aims: This study examines the conjoint trajectories of depressive symptoms and delinquent behavior from adolescence (age 14) into young adulthood (age 24) as predictors of substance use disorders (SUDs) in adulthood (age 32). Methods: Of the 816 participants, 52% were African Americans, and 48% were Puerto Ricans. After we obtained the conjoint trajectory groups using Mplus, we performed logistic regression analyses using SAS to compare the Bayesian Posterior Probability ( BPP ) of each of the conjoint trajectory groups with the BPP of the reference conjoint trajectory group to predict SUDs. Results: Four conjoint trajectory groups were obtained. The higher BPPs of both the high depressive symptoms and low delinquent behavior trajectory group ( AOR = 3.54, p < .05) and the medium depressive symptoms and high delinquent behavior trajectory group ( AOR = 10.28, p < .001), as compared with the BPP of the low depressive symptoms and low delinquent behavior trajectory group, were associated with an increased likelihood of SUDs in adulthood. These associations were maintained with control on gender, ethnicity, the use of alcohol, cigarettes, and marijuana, socioeconomic status (SES) at age 14, and income and educational level at age 36. Conclusions: Prevention and treatment of delinquent individuals reporting SUDs might be more effective if their depressive symptoms were also addressed. Similarly, prevention and treatment of depressed individuals reporting SUDs might be more effective if their delinquent behavior was also addressed. Highlights: First study of conjoint trajectories of depression & delinquency as related to SUDS Treatment of depressed individuals reporting SUDS should address their delinquency. Treatment of delinquent individuals reporting SUDS should address their depression.